The roles of TGFβ in the tumour microenvironment - Pickup, Michael (2013)
The influence of the microenvironment on tumour progression is becoming clearer. In this Review we address the role of an essential signalling pathway, that of transforming growth factor-β, in the regulation of components of the tumour microenvironment and how this contributes to tumour progression.